A factor risk model with reference returns for the US dollar and Japanese yen bond markets - Carlos Bernadell; Joachim Coche; Ken Nyholm (European Central Bank (ECB), 2006)
This paper develops a new methodology for simulating fixed-income return distributions. It is shown that a traditional factor risk model, when augmented with reference returns, is capable of generating visually consistent return distributions for a broad range of fixed income instruments such as government and nongovernment instruments in the US dollar and Japanese yen bond markets. The reference returns result from a regime-switching Nelson-Siegel yield curve model following Bernadell, Coche and Nyholm (2005). Empirical results are encouraging: simulated distributions exhibit most characteristics observed in the fixed income markets such as non-normal right-skewed distributions for short maturity instrument while instruments with longer maturity are closer to being normally distributed.
Keywords: C15; C32; C53; G11; G15; 330; factor risk model; Regime switching; scenario analysis; Portfolio-Management; Risiko; Anleihe; Yen; US-Dollar